2019
DOI: 10.1017/s002237781900062x
|View full text |Cite|
|
Sign up to set email alerts
|

Direct construction of optimized stellarator shapes. Part 3. Omnigenity near the magnetic axis

Abstract: The condition of omnigenity is investigated, and applied to the near-axis expansion of Garren and Boozer (1991a). Due in part to the particular analyticity requirements of the near-axis expansion, we find that, excluding quasi-symmetric solutions, only one type of omnigenity, namely quasi-isodynamicity, can be satisfied at first order in the distance from the magnetic axis. Our construction provides a parameterization of the space of such solutions, and the cylindrical reformulation and numerical method of Lan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
101
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(107 citation statements)
references
References 19 publications
6
101
0
Order By: Relevance
“…We have argued recently Landreman, Sengupta & Plunk 2019;Jorge, Sengupta & Landreman 2020a) that this asymptotic approach deserves further attention, as it complements numerical optimization. The asymptotic approach allows equilibria to be evaluated orders of magnitude faster, and it provides a practical way to generate new initial conditions for numerical optimization Plunk, Landreman & Helander 2019). In the present paper, we extend our asymptotic approach, which has focused previously on neoclassical confinement, to MHD stability.…”
Section: Introductionmentioning
confidence: 98%
“…We have argued recently Landreman, Sengupta & Plunk 2019;Jorge, Sengupta & Landreman 2020a) that this asymptotic approach deserves further attention, as it complements numerical optimization. The asymptotic approach allows equilibria to be evaluated orders of magnitude faster, and it provides a practical way to generate new initial conditions for numerical optimization Plunk, Landreman & Helander 2019). In the present paper, we extend our asymptotic approach, which has focused previously on neoclassical confinement, to MHD stability.…”
Section: Introductionmentioning
confidence: 98%
“…'direct construction' of optimal solutions), is potentially beneficial due to the speedup offered (Landreman, Sengupta & Plunk 2019). So far, the only ways to do this have involved approximations to the problem such as a small distance from the magnetic axis (Garren & Boozer 1991a,b;Landreman & Sengupta 2018;Landreman et al 2019;Plunk, Landreman & Helander 2019), or a small deviation from axisymmetry (Plunk & Helander 2018). However, solving these approximate problems can also lead to fundamental insights into the properties of the solutions, and the size of the solution space.…”
Section: Introductionmentioning
confidence: 99%
“…(2019) and Plunk et al. (2019). However, this approach of setting turns out to require modification when applied to the equations.…”
Section: Generating a Finite-minor-radius Boundarymentioning
confidence: 97%
“…The near-axis expansion, although it is an approximation, is always accurate in the core of any stellarator, even stellarators for which the aspect ratio of the outermost surface is not large. In a recent series of papers (Landreman & Sengupta 2018; Landreman, Sengupta & Plunk 2019; Plunk, Landreman & Helander 2019), the near-axis expansion was developed into practical procedures for constructing fields with quasisymmetry, or the more general condition of omnigenity. It was also shown that, close to the axis, quasisymmetric configurations obtained by conventional optimization closely match configurations generated by the construction (Landreman 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation